مستوى الكفاءة الذاتية لدى طلبة الدراسات العليا وفق بعض المتغيرات - محمد , حسـنية محمـد آدم; عبدالكريم, صالحة محمد يونس (Al-Qurtas, 2025)
مستوى الكفاءة الذاتية لدى طلبة الدراسات العليا وفق بعض المتغيرات